2021
DOI: 10.1016/j.bbrc.2021.02.114
|View full text |Cite
|
Sign up to set email alerts
|

Interdomain linkers tailor the stability of immunoglobulin repeats in polyproteins

Abstract: Linkers in polyproteins are considered as mere spacers between two adjacent domains. However, a series of studies using single-molecule force spectroscopy have recently reported distinct thermodynamic stability of I27 in polyproteins with varying linkers and indicated the vital role of linkers in domain stability. A flexible glycine rich linker (-(GGG)n, n≥3) featured unfolding at lower forces than regularly used arg-ser (RS) based linker. Interdomain interactions among I27 domains in Gly-rich linkers were sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…As interdomain linkers are known to alter the stability and flexibility of protein monomer units in polyproteins, we should have control over the sequence and length of the linker. 23,59,60 Furthermore, these linkers are a potential active site for SortaseA or ligase OaAEP1 and prevent the growth of polyprotein formation and degrade the product back to its monomers. These methods provide highly dispersed polyproteins.…”
Section: Post-translational Methods Of Polyprotein Synthesis (Protein...mentioning
confidence: 99%
See 1 more Smart Citation
“…As interdomain linkers are known to alter the stability and flexibility of protein monomer units in polyproteins, we should have control over the sequence and length of the linker. 23,59,60 Furthermore, these linkers are a potential active site for SortaseA or ligase OaAEP1 and prevent the growth of polyprotein formation and degrade the product back to its monomers. These methods provide highly dispersed polyproteins.…”
Section: Post-translational Methods Of Polyprotein Synthesis (Protein...mentioning
confidence: 99%
“…A presumption in these studies is the independent response of individual domains to mechanical perturbations. However, independent research groups across the globe have recently identified cooperativity in the folding dynamics of domains in a polyprotein using force-spectroscopy, [21][22][23][24] indicating the potential of SMFS as a tool to study the physical properties of polyproteins. It is noticed that the interdomain linkers in polyprotein constructs play a pivotal role in inducing cooperativity.…”
Section: Introductionmentioning
confidence: 99%